PROPERTY AND FREE INITIATIVE IN ECONOMY - Viorel CORNESCU; Cristina CHIRIAC (Challenges of the Knowledge Society)
The property is a subject that has been and it is studied by specialists from the economics, philosophy, law, history fields etc. It is natural to be a subject of attraction since the property is an essential precondition of the human economic activity, activity that provides the basis of his existence and creates the foundation for the other human activities. As between economics and law – how everybody knows – exists a close interdependence, it is necessary to explain this interdependence from the property perspective, as well as the relationship between property - economic liberty - free initiative. A clarification of ideas about these things and theoretical aspects, from economic and legal point of view, we believe that will have a benefic effect for the economical, legal and political practice etc.